Control of the size and density of ZnO-nanorods grown onto graphene nanoplatelets in aqueous suspensions. Issue 86 (5th September 2016) - Chandraiahgari, C. R.; De Bellis, G.; Balijepalli, S. K.; Kaciulis, S.; Ballirano, P.; Migliori, A.; Morandi, V.; Caneve, L.; Sarto, F.; Sarto, M. S.
Abstract : Zinc oxide nanorods with controlled density and size and high chemical purity were grown onto unsupported graphene nanoplatelets in aqueous suspension. Abstract : Zinc oxide nanorods (ZnO-NRs) with high density and chemical purity were grown onto unsupported graphene nanoplatelets (GNPs) in aqueous suspensions, using two different growth approaches namely: a hydrothermal method and ultrasonic probe sonication. The size and density of the ZnO-nanorods grown onto graphene nanoplatelets were controlled through seed layer deposition and through the proper setting of the process parameters, in particular through the control of the fluidodynamics of the colloidal suspension during the growth. The highest growth density of the ZnO nanorods having a diameter of ∼45 nm was obtained onto GNPs seeded by the probe sonication method and through the hydrothermal method in dynamic conditions. XRD and XPS investigations confirmed that all produced ZnO-GNP composites are characterized by high crystallinity and purity, although solution dynamics affected their UV luminescence. The proposed approaches enable the controlled high-density growth of crystalline ZnO-NRs onto GNPs in an aqueous suspension, at a low cost, and are suitable for large scale production.